(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
In this article we will talk about the formation of children’s communication with others, the means of communication, responsibility, self-criticism, a creative approach to solving problems, a correct and adequate assessment of their strengths. One of the main conditions for conducting lessons in a preschool educational institution is the use of interactive teaching methods and the activation of the mental activity of children at all stages of the lesson